ZnxSn1-xS thin films: A study on its tunable opto-electrical properties for application towards a high efficient photodetector. (August 2020) - Barman, Biswajit; Bangera, Kasturi V.; Shivakumar, G.K.
Graphical abstract: Highlights: ZnSnS films were thermally grown for the first time to the best of our knowledge. The photodetector behavior of the film (Zn ≤ 0.40) is reported for the first time. Band gap of the films can be tuned from 3.49 to 1.54 eV by varying the Zn content. The Zn0.1 Sn0.9 S film exhibited the highest photosensitivity of 43.38. Abstract: Zinc sulfide (ZnS) and tin sulfide (SnS) are crucial semiconductors with potential use in various opto-electronic applications. By incorporating ZnS and SnS to form Znx Sn1-x S thin film, one can expect exceptional opto-electrical properties due to their large band gap dissimilarity. Herein, thin films of Znx Sn1-x S (0.0 ≤ x ≤ 1.0) were successfully deposited on glass substrates using a thermal evaporation method for the first time and its various properties were analyzed. X-ray diffraction (XRD) analysis confirmed the polycrystalline behavior of Znx Sn1-x S films with a preferred orientation along the (1 1 1) plane. The absence of any secondary peaks along with the shift in the (1 1 1) peak position to lower 2θ values with increasing Zn concentration confirmed the formation of a solid solution. SEM analysis depicted the presence of uniform and homogeneous films. The formation of nearly stoichiometric Znx Sn1-x S films was verified using an energy dispersive spectroscopy (EDS). The electrical and optical properties of the films were estimated from the two-probe method and UV–Vis spectroscopy, respectively. The energy band gap values decreased from 3.49 eV to 1.54 eV as the composition of the Znx Sn1-x S films was varied. The various opto-electrical parameters were investigated and the photosensitivity was found highest at 43.38 for the Zn0.10 Sn0.90 S films. The observed tunable opto-electrical properties of the Znx Sn1-x S films suggests that the films can be utilized for a wide range of opto-electronic applications.